Nutritional and Nonnutritional Content of Underexploited Edible Seaweeds. (15th October 2022) - Alghazeer, Rabia; El Fatah, Hesham; Azwai, Salah; Elghmasi, Sana; Sidati, Maammar; El Fituri, Ali; Althaluti, Ezdehar; Gammoudi, Ftaim; Yudiati, Ervia; Talouz, Nadia; Shamlan, Ghalia; AL-Farga, Ammar; et al.
Abstract : Macroalgae are a valuable source of highly bioactive primary and secondary metabolites that may have useful bioapplications. To investigate the nutritional and nonnutritional contents of underexploited edible seaweeds, proximate composition, including protein, fat, ash, vitamins A, C, and E, and niacin, as well as important phytochemicals, including polyphenols, tannins, flavonoids, alkaloids, sterols, saponins, and coumarins, were screened from algal species using spectrophotometric methods. Ash content ranged from 3.15–25.23% for green seaweeds, 5–29.78% for brown algae, and 7–31.15% for red algae. Crude protein content ranged between 5 and 9.8% in Chlorophyta, 5 and 7.4% in Rhodophyta, and between 4.6 and 6.2% in Phaeophyceae. Crude carbohydrate contents ranged from 20 to 42% for the collected seaweeds, where green algae had the highest content (22.5–42%), followed by brown algae (21–29.5%) and red algae (20–29%). Lipid content was found to be low in all the studied taxa at approximately 1–6%, except for Caulerpa prolifera (Chlorophyta), which had a noticeable higher lipid content at 12.41%. These results indicated that Phaeophyceae were enriched with a high phytochemical content, followed by that of Chlorophyta and Rhodophyta. The studied algal species contained a high amount of carbohydrate and protein, indicating that they could be considered as a healthy food source.